As mães na produção do cuidado à pessoa com deficiência: uma cartografia na cidade de João Pessoa - PB - Menezes, Tarcisio Almeida (2021)
Introduction: The care for People with Disabilities (PwD) is mainly performed by women, with the mother being the main provider. In the centrality of these charges, culturally imposed, women produce several existential connections to guarantee the care of the other, in different contexts, through the articulation of institutional networks and Living Networks. The study of the movements constructed by women, mothers of PwD, in the exercise of caring for themselves and their children contributes to the understanding of the fabric of their own networks of sociability and care. Objective: The present study aims to analyze the agencies for the production of care operated by mothers of PwD, in the city of João Pessoa - PB, in their daily experiences. Method: For this, a cartography of the care productions of these mothers was carried out, from a qualitative approach, in an exploratory and analytical study. Several cartographic devices were used, which allowed the tracking of the affections and tensions that the encounter with the “others” had for the production of care for PwD by their mothers, such as: conversations with mothers who have children with disabilities, in-depth virtual interview with one of them, and the geoprocessing mapping of the network. All productions were recorded in a cartographic diary and processed in a research group. Results: The cartographic route resulted in three (03) products, which are: (i) a mapping of health institutions, showing access and barriers of the specialized network in the care of PwD in the Unified Health System in João Pessoa; (ii) a theoretical-methodological discussion about the power of mothers as guides for the study of care production for their children; and (iii) the cartography of the movements of a guide mother as an effective Rede Viva in production to guarantee the care of herself and her disabled child. Conclusions: Given the above, it was possible to deepen the theoretical methodologically the concept-mother-guide tool for the discussion of care networks for PwD. Along this path, there was evidence of movements between the institutional and living networks built by mothers of PwD who are crossed by different power relations. With regard to the joints that happen to guarantee the care operated by PwD mothers, there are territorial barriers and the power of inventive care productions that are not linked to the clinical diagnosis and that, in the event, are being woven, assembled and disassembled, in a living process.